Effect of platelet concentrates on the treatment outcome of peri implantitis: A systematic review - Nikitha Ravindra Shetty; K B Menaka (Journal of Indian Society of Periodontology, 2023)
Platelet concentrates (PCs) are biological agents known to promote soft as well as hard tissue healing. The review aimed at evaluating the effectiveness of PCs for treating peri-implantitis (PI). Five electronic databases were systematically reviewed followed by a handsearch of relevant journals. The selected studies focused on the predetermined primary and secondary outcomes. The primary outcomes were bleeding on probing, probing depth, marginal bone level. RevMan 5.4.1 software was used for risk bias analysis. The search retrieved 12 articles, and only one study compared PC and open flap debridement. Other three studies with different control arms were included to evaluate the overall effect of different PCs in treatment of PI. High heterogeneity was found regarding study design, sample size, surgical techniques, and methods for preparing PCs. The use of platelet-rich fibrin for PI over conventional therapy was beneficial in improving clinical parameters. In addition, PC when combined with graft materials provided a significant improvement in parameters assessed. The preliminary data regarding the use of different PC in treatment of PI seem to be promising. However, due to lack of comparative randomized controlled trials, future clinical research is necessary to comment on the role of PCs for treating PI.